Antimicrobial Mechanism and Secondary Metabolite Profiles of Biocontrol Agent Streptomyces lydicus M01 Based on Ultra-High-Performance Liquid Chromatography Connected to a Quadrupole Time-of-Flight Mass Spectrometer Analysis and Genome Sequencing - Wang, Mingxuan; Li, Jing; Cong, Wenjie; Zhang, Jianguo (Frontiers in Microbiology, 2022)
Streptomyces lydicus was used as biopesticides for crop protection in agriculture, however, the antimicrobial mechanism remains unclear and no systematic research on the secondary metabolites of S. lydicus has been reported. In this study, the extract of S. lydicus M01 culture was used to treat plant pathogen Alternaria alternata and morphological changes in the plasma membrane and cell wall of hyphae and conidia were observed. Fluorescence microscopy combined with different dyes showed that the accumulation of reactive oxygen species and cell death were also induced. To investigate the secondary metabolites in the culture filtrate, an online detection strategy of ultra-high-performance liquid chromatography connected to a quadrupole time-of-flight mass spectrometer (UPLC-Q-TOF-MS) was used for identification. The results revealed in excess of 120 metabolites, mainly consisted of fungicides, antibacterial agents, herbicides, insecticides and plant growth regulator such as IAA. Among which the 5 dominant components were oxadixyl, chloreturon, S-metolachlor, fentrazamide and bucarpolate. On the other hand, the complete genome of S. lydicus M01 was sequenced and a number of key function gene clusters that contribute to the biosynthesis of active secondary metabolites were revealed. This is the first systematic characterization of S. lydicus secondary metabolites, and these results offer novel and valuable evidence for a comprehensive understanding of the biocontrol agent Streptomyces lydicus and its application in agriculture.